2017
DOI: 10.1161/circheartfailure.116.003594
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Pressures Measured Using an Implantable Hemodynamic Monitor

Abstract: Background-The purpose of this analysis was to examine whether implantable hemodynamic monitor-derived baseline estimated pulmonary artery diastolic pressure (ePAD) and change from baseline ePAD were independent predictors of all-cause mortality in patients with chronic heart failure. Methods and Results-Retrospective analysis used data from 3 studies (n=790 patients; 216 deaths). Baseline ePAD was related to mortality using a multivariable model including baseline and demographic data. Changes in ePAD defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…25 Borlaug and colleagues 26 showed that elevated PCWP during exercise can distinguish patients with HFpEF from those with noncardiac dyspnea, and the rise in PCWP during exercise is an important pathophysiologic determinant of HFpEF early in the course of the clinical syndrome. PCWP during exercise also correlates with 6-minute walk test distance and is an important determinant of mortality in patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…25 Borlaug and colleagues 26 showed that elevated PCWP during exercise can distinguish patients with HFpEF from those with noncardiac dyspnea, and the rise in PCWP during exercise is an important pathophysiologic determinant of HFpEF early in the course of the clinical syndrome. PCWP during exercise also correlates with 6-minute walk test distance and is an important determinant of mortality in patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Supervision protocols and treatment algorithms have been published previously. 6,7,[20][21][22] The majority of medication changes in MEMS-HF was due to dose increases of diuretics [1068 medication changes compared with 312 changes in angiotensin-converting enzyme (ACE) inhibitors, 209 changes in beta-blockers, and 170 changes in mineralocorticoid antagonists]. For diuretic dose equivalents in furosemide (loop diuretics) or metolazone (thiazides), see Table 1.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…4 Pulmonary artery pressure (PAP) rises days and weeks before clinical signs and symptoms develop, 5 and early treatment with diuretics might be a tool to prevent hospitalizations. 6 It has been shown that titration of heart failure medications guided by haemodynamic parameters collected remotely (CardioMEMS HF System) is feasible, 7 reduces hospitalization, and improves quality of life. 8,9 Recently, outcomes from studies using the angiotensin receptor blocker/neprilysin inhibitor sacubitril/valsartan and studies with the sodium-glucose transporter 2 inhibitors (SGLT2i) dapagliflozin 10 and empagliflozin 11 have shown a reduction in cardiovascular death and hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of HF readmissions are due to fluid overload, and the process of decompensation may be prevented if clinical parameters are strictly controlled via telemedical monitoring [14,15]. The likelihood of adverse clinical outcomes increases when pulmonary artery pressure (PAP) rises, usually days to weeks before clinical manifestations of HF [16,17]. A wireless monitoring system (CardioMEMS™) detecting changes in PAP has been proposed for HF patients.…”
Section: Introductionmentioning
confidence: 99%